Prevalence and Risk of Schizophrenia and Bipolar Disorder in Patients with Type 1 Diabetes Mellitus: A Systematic Review and Meta-analysis - Sindhu Toomukuntla; Chandra Vamshi Vemula; Mamidipalli Sai Spoorthy; Syed Ahmed Zaki; Sai Krishna Tikka (Indian Journal of Psychological Medicine)
Purpose of the Review: Schizophrenia and bipolar disorder are understood to have neuroinflammatory/neuro-immunological basis in their etiopathogenesis. There are few studies synthesizing the association of schizophrenia and bipolar disorder in type 1 diabetes mellitus (T1DM), a common immunological disorder. Collection and Analysis of Data: We performed meta-analyses of studies assessing the prevalence and risk of schizophrenia and related disorders and bipolar disorder in individuals with T1DM. Fifteen studies consisting of a total sample of 9,768,028 (T1DM: 435,553; non-T1DM controls: 9,332,475) were included. Random-effects meta-analyses using the restricted maximum likelihood method for pooling logit transformed prevalence values and the Mantel–Haenszel test for pooling risk ratios were used. I 2 statistic and the rank correlation test for Funnel plots’ asymmetry were used to assess heterogeneity and publication bias, respectively. Results: Pooled (transformed-back-transformed) prevalence for schizophrenia and related psychotic disorders was 0.37% (95%CI: 0.19–0.73), and for bipolar disorder it was 0.39% (95%CI: 0.05–2.99) (together: 0.38% (95%CI: 0.2–0.71)] in T1DM. The prevalence models showed significant heterogeneity but were statistically significant, had low publication bias, and survived sensitivity analysis. The pooled risk ratio for schizophrenia and related disorders together with bipolar disorder was 1.80 (95%CI: 0.64–5.03), and for schizophrenia and related disorders alone it was 1.19 (95%CI: 0.46–3.11), indicating higher rates of these disorders in T1DM. The pooled risk ratios were not statistically significant and did not survive sensitivity analysis. Trial sequential analysis suggested the need for more studies to confirm increased risk. Conclusion: With available studies, we could not provide convincing evidence for the hypothesis that the prevalence and risk of schizophrenia and related disorders and bipolar disorder are significantly greater in individuals with T1DM.